Financial Technology (FinTech) and Its Impact on Financial Performance of Islamic Banking - Siska, Elmira (Forum Kerjasama Pendidikan Tinggi, 2022)
As a financial services provider, Islamic banking must be able to keep up with the times by responding to challenges and establishing a competitive advantage through the development of innovative financial products and services using Fintech. The goal of this research is to examine how FinTech services affect Islamic banking's financial performance. With a case study at Bank Syariah Indonesia (BSI), this study used a quantitative-descriptive research design. Financial ratios such as CAR, ROA, ROE, BOPO, FDR, and Finctech service were used as secondary data. The data is in annual time series format ranging from 2016 to 2020. In this study, the program SPSS 21 was used to process the data to perform the Classical Assumption Test, Simple Linear Regression, t-Test, and Coefficient of Determination Test. Finding of current research proves that Fintech service has an impact on the financial performance of BSI in terms of CAR, ROA, ROE, BOPO, and FDR